PENGARUH TINGKAT SUKU BUNGA, INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP NILAI TUKAR RUPIAH ATAS DOLAR AS - Ramadhan, Masri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2019)
The purpose of this study was to analyze the effect of the Interest Rates (X1), Inflation (X2), Growth (X3) of the Exchange Rate on the US Dollar (Y). The data used is secondary data or Time Series from 1977 until 2016 ata sample of 40 Years. This study uses multiple regression formula: Y = a + b1x1 + b2X2 + b3X3 + e. The results of the study using SPSS version 20.1 can be seen that the determinant coefficient (R) of 0.6580, while the value of RSquare amounted to 0.433, which means that the contribution of variable interest rates, inflation and economic growth on the exchange rate on the US dollar was at 43.33 % and the rest influenced by other variables. The results of this study found that the variable interest rate (X1) and economic growth (X3) and significant impact on the exchange rate on the US dollar. As for the inflation variable (X2) but not significant effect on the rupiah against the US dollar